Single And Binary Adsorption Of Phenol And 3-Chlorophenol Onto Granular Activated Carbon. - Maarof, Hawaiah Imam; Hameed, Bassim H.; Ahmad, Abdul Latif (2004)
Removal of phenol and 3-chlorophenol from single and bisolute diluted aqueous solution through adsorption on commercial granular activated carbon were experimentally investigated.